VISUALIZATION OF AR ROS'S CHINESE CHEONGSAM THROUGH FASHION PHOTOGRAPHY AS A CULTURAL REPRESENTATION OF THE BAKAR TONGKANG RITUAL - M. Luthfi; Tira Thania; Ivan Saputra; Haslinda Mora (Journal of Social Science, 2026)
Objective: This creation research aims to visualize Ar Ros's Cheongsam through fashion photography in order to represent its aesthetic characteristics, cultural identity, and visual appeal. Method: The creation process involved observation, literature study, interviews, concept development, model selection, studio lighting arrangement, and digital imaging techniques. The visual concept was developed by combining Chinese cultural elements, symbolic color schemes, traditional properties, and controlled studio lighting. Results: The results consist of twenty-four fashion photography works that successfully present the beauty of the Cheongsam while communicating the cultural values embedded in the Bakar Tongkang motif. Novelty: The novelty of this work lies in the integration of local cultural identity and fashion photography as a medium for cultural promotion, visual documentation, and cultural preservation within the contemporary creative industry.